Compensation Phenomenon and Hysteresis Loops of a Mixed Spin Ferrimagnetic System - Hadey Mohamad; Anwar G. Thejeel (مجلة علوم ذي قار)
A ferrimagnetic mixed-spin simple cubic system consisting of spin-3/2 and spin-9/2 constituents on two interpenetrating sublattices was investigated using the molecular mean-field approximation based on the Blume-Capel Ising model. The influence of crystal fields and external magnetic fields on magnetic ordering was systematically analyzed by solving the coupled self-consistent equations for sublattice magnetizations. Crystal field anisotropy significantly modifies the magnetic exchange interactions, where specific values of DA/|J| = -13.5 and DB/|J| = -6.75 induce compensation phenomena through differential thermal responses of the sublattices. At these critical values, the system exhibits zero net magnetization while maintaining long-range ferrimagnetic order (mA = -mB ≠ 0). The application of external magnetic fields generates distinct hysteresis behaviors, including multi-step magnetization processes with triple-loop configurations that systematically transform with increasing temperature. These hysteresis patterns undergo progressive changes from multi-loop structures to singular central loops before complete dissipation at higher temperatures, reflecting the complex interplay between crystal field anisotropy, exchange interactions, and thermal fluctuations. The results demonstrate how crystallographic anisotropy parameters can be tuned to control both compensation temperatures and hysteresis characteristics in mixed-spin ferrimagnetic systems.